Menace of Internet Fraud on Nigeria Youth: Lesson from the Indonesia Experience - Aidonojie, Paul Atagamen; Jufri, Muwaffiq; Mustafa , Mundu; Eregbuonye, Obieshi; Wakili Abacha, Saminu (Jurnal Mengkaji Indonesia, 2024)
Abstract: The quest for fast wealth acquisition through internet fraud among the Nigerian youth has become a common lifestyle. That education among the Nigerian youth is considered a scam, given the poor economic level of the country and the inability to secure a job after graduation. Although several laws prohibit internet fraud in Nigeria, there seems to be a surge of internet fraud and a setback in educational focus among the Nigerian youth. However, Indonesia though has similar challenges but has been able to surmount and curtail incidences of fraud. Purpose: In this regard, this study tends to examine the menace of internet fraud in shackling the Nigerian youth from an educational focus and how the Nigerian government can learn from the Indonesian experience in curbing the incidence of fraud through legal and educational policy. Design/Methodology/Approach: The study adopts a doctrinal method of study; primary and secondary sources of authority were relied on in sourcing for data. The data obtained was analysed using a descriptive and analytical method of study. Findings: The study therefore found that the prevalence of internet fraud among Nigerian youth is as a result of unemployment, poverty, poor educational policy, and the syndrome of getting rich quickly through internet fraud. The study further found that the educational process among Nigerian youth has been severely affected due to the prevalence of internet fraud. Also, it was also revealed that the Indonesian government through effective legal, educational, and socio-economic policy has been able to curtail the incidence of internet fraud among its youths. Originality/value: The study therefore contributes to the existing body of knowledge as it concerns curtailing the incidence of fraud and enhancing education. Furthermore, the study also achieves a high focus on education among the Nigerian youth by identifying the fact that the Nigerian government needs to incorporate the Indonesian government's legal and educational policy that tends to promote education among its youth. This will also result in a cross-cultural ideology in resolving the menace of internet fraud.